Bulk Heterojunction Solar Cells: A Mechanistic Understanding of Processing Additive‐Induced Efficiency Enhancement in Bulk Heterojunction Organic Solar Cells (Adv. Mater. 2/2014). (January 2014) - Schmidt, Kristin; Tassone, Christopher J.; Niskala, Jeremy R.; Yiu, Alan T.; Lee, Olivia P.; Weiss, Thomas M.; Wang, Cheng; Fréchet, Jean M. J.; Beaujuge, Pierre M.; Toney, Michael F.
<x xml:space="preserve">Abstract</x> The introduction of processing additives is widely used to increase power conversion efficiencies in organic solar cells. Michael F. Toney, Jeremy R. Niskala and co‐workers show on page 300 how additives change the polymer conformation in the casting solution leading to a more‐intermixed phase‐segregated network structure of the organic solar‐cell active layer. This results in a five‐fold enhancement in efficiency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>